GLP-1 Receptor: A New Target for Sepsis - Yang, Fuxun; Zeng, Fan; Luo, Xiaoxiu; Lei, Yu; Li, Jiajia; Lu, Sen; Huang, Xiaobo; Lan, Yunping; Liu, Rongan (Frontiers in Pharmacology, 2021)
Patients with sepsis often exhibit hyperglycemia, which increases mortality. GLP-1 receptor agonists (GLP-1RAs) not only regulate blood glucose homeostasis but also improve organ dysfunction, regulate immunity, and control inflammation and other functions in patients with sepsis. Here, we review the possible application of GLP-1RAs in sepsis, to provide a new perspective for the clinical diagnosis and treatment of patients with sepsis complicated with stress hyperglycemia.